A case series of Merkel cell carcinoma of the eyelid: a rare entity often misdiagnosed. (3rd September 2019) - Iuliano, Adriana; Tranfa, Fausto; Clemente, Lidia; Fossataro, Federica; Strianese, Diego
ABSTRACT: Merkel cell carcinoma (MCC) is one of the rarest eyelid tumors, with high mortality rate due to lymphatic and metastatic spread. We hereby report six cases of patients with histological diagnosis of MCC referred to our Orbit Unit between 2012 and 2018, focusing on diagnosis, treatment, and subsequent follow up. All patients underwent surgical excision and systemic work-up. Both MCC TNM and eyelid MCC TNM were used to stage lesions. MCC of the eyelid is usually misdiagnosed as benign or other malignant lesions. A prompt examination and a wide local excision are mandatory. A close follow-up of these patients is advised due to high recurrence rate and lymphatic spread.